Does the Histopathologic Pattern of the Ureteropelvic Junction Affect the Outcome of Pyeloplasty? - Issi, Oktay; Deliktas, Hasan; Gedik, Abdullah; Ozekinci, Selver; Bircan, Mehmet Kamuran; Sahin, Hayrettin (Urology Journal, 2015)
Abstract Purpose: To investigate the effects of the histopathologic pattern of obstructed ureteropelvic junction (UPJ) specimens, including collagen type 3, elastin, fibrosis and Cajal cells, on the outcome of pyeloplasty. Materials and Methods: Histopathological specimens obtained following Anderson-Hynes pyeloplasty from 52 patients with intrinsic ureteropelvic junction obstruction (UPJO) between January 2005 and January 2008 were evaluated histopathologically. Patients with extrinsic or secondary UPJO were excluded. Preoperative and postoperative radiographic evaluations were performed either via diuretic renography or intravenous pyelography, or both. Six months post-surgery the patients were divided into 2 groups, as successful surgery (group 1) and unsuccessful surgery (group 2). Histopathological findings (collagen type 3, elastin, fibrosis and Cajal cells) in each group were statistically compared. Results: The study included 52 patients (21 female and 31 male). Mean age of the entire study population was 39.42 ± 14.5 years, versus 39.63 ± 14.9 years in group 1 (n = 47) and 37.4 ± 10.0 years in group 2 (n = 5). Median follow-up was 18 months. There weren't any significant differences in collagen type 3, elastin, fibrosis, or Cajal cells between the 2 groups (P > .05). Conclusion: The histopathologic pattern of UPJ was not a factor associated with the success of pyeloplasty. Based on the present findings, we conclude that surgical technique is more important than the histopathologic pattern of UPJ for the successful treatment of UPJO.